Large vessel vasculitis and the rising role of FDG PET-CT: A case report and review of literature - AlNuaimi, Dana (Radiol Case Rep, 2020)
Giant cell arteritis (GCA) is a rare form of large and medium vessel vasculitis affecting about 20 cases per 100,000 persons older than the age of 50 years. GCA results in inflammation and constriction of the temporal arteries, cranial arteries, the aorta, and its major branches. Patients often present with vague constitutional symptoms and fever of unknown origin. GCA is a medical emergency requiring prompt diagnosis and early treatment with glucocorticoids which is essential to avoid irreversible end organ damage such as loss of vision, stroke and aneurysm formation. We report a case of a 63-year-old male patient presenting to our healthcare facility with sudden loss of vision and an ischemic brain infarct to be finally diagnosed as a case of giant cell arteritis with positron emission tomography-computed tomography imaging used to evaluate the full extent of the involved vasculature. Diagnostic imaging with FDG positron emission tomography-computed tomography can play a crucial role in the diagnosis, evaluation of the full burden of the disease and follow up to the response of therapy.